Effects of renal sympathetic denervation on myocardial structure, function and perfusion: A serial CMR study. (May 2018) - Delacroix, Sinny; Chokka, Ramesh G.; Nelson, Adam J.; Wong, Dennis T.; Pederson, Stephen; Nimmo, Joanne; Rajwani, Adil; Williams, Kerry; Teo, Karen S.; Worthley, Stephen G.
Abstract: Background and aims: Echocardiographic studies have shown improvements in cardiac indices associated with renal sympathetic denervation (RDN), however, the benefits on myocardial perfusion have never been assessed. This trial was designed to study the effects of RDN on myocardial perfusion using cardiac magnetic resonance (CMR) imaging. Methods: A total of 14 patients with resistant hypertension were recruited for RDN and myocardial perfusion, alongside other CMR indices, was assessed at baseline and at 6 months. Results: RDN showed significant reduction of mean office blood pressures from 181/100 ± 19/16 mmHg to 147/85 ± 19/17 mmHg, 6 months after the procedure ( p  < 0.0001). This was combined with significant improvement in regional aortic distensibility ( p  < 0.02) and associated with trends of improved myocardial perfusion reserve index (baseline = 2.2 ± 1; 6 months = 2.9 ± 1 units) ( p  = 0.08). Left ventricular end systolic volume index decreased from baseline to 6 months post procedure, 27 ± 13 ml/m 2 vs. 22 ± 10 ml/m 2 ( p  = 0.03), but there was no significant change in left ventricular end diastolic volume index ( p  = 0.09). There was significant improvement in mean left ventricular ejection fraction from 68 ± 10% to 72 + 9%, 6 months post procedure ( p  = 0.04). T1 mapping failed to detect fibrosis in these patients at baseline and therefore no change was noted, however, extracellular volume percent improved from 46 ± 4% at baseline to 41 ± 8% at 6 months ( p  = 0.002). Conclusions: This study demonstrates that renal sympathetic denervation increased myocardial perfusion by 32% as assessed by CMR, and, this was associated with improvements in cardiac volumes and function. Larger well controlled and randomized studies are required to assess the clinical significance of these findings. Highlights: The additive value of cardiovascular magnetic resonance indices in defining the effects of renal denervation is proposed. Improvements in standard cardiac indices noted post renal sympathetic denervation. Above changes accompanied with improvements in cardiac perfusion and aortic stiffness post procedure.